2010
DOI: 10.1002/nau.20929
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent catheterization with hydrophilic catheters as a treatment of chronic neurogenic urinary retention

Abstract: There is a wealth of evidence, including randomized controlled trials, to support the benefits of hydrophilic catheters in terms of safety and quality of life, especially in men with spinal cord injury. More data are required for spina bifida, multiple sclerosis, and in women. Further research is warranted, especially large-scale and long-term robust comparisons of different types of catheter, and in well-defined and stratified populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 59 publications
0
46
1
3
Order By: Relevance
“…CIC is an effective long-term urinary management strategy that maintains continence and reduces urinary tract complications 15 , and as such is currently the most preferred method for the management of neurogenic bladder in patients with SCI. Cameron et al 16 reported that use of CIC increased from about 13% in 1972 to 56% in 1991.…”
Section: Discussionmentioning
confidence: 99%
“…CIC is an effective long-term urinary management strategy that maintains continence and reduces urinary tract complications 15 , and as such is currently the most preferred method for the management of neurogenic bladder in patients with SCI. Cameron et al 16 reported that use of CIC increased from about 13% in 1972 to 56% in 1991.…”
Section: Discussionmentioning
confidence: 99%
“…15 The use of hydrophilic catheters has been reported to reduce urethral trauma and complications. 13 However, the current evidence is limited, especially regarding the optimal catheter type for decreasing the occurrence of urethral complications and urinary tract infections. 16 The occurrence rate of urethral strictures in men using IC was significantly higher (25 vs 14%) and the odds of an urethral stricture were twice the odds in men using other bladder evacuation methods.…”
Section: Discussionmentioning
confidence: 99%
“…The catheter surface has been claimed to be an important factor in the development of urethral strictures. 12,13 However, there is a lack of current data concerning the occurrence and characteristics of urethral strictures in men with NLUTD using IC since the wide-spread use of hydrophilic catheters.…”
Section: Introductionmentioning
confidence: 99%
“…Although newer data and expert panels are in favor of single-use hydrophilic catheters in an aseptic or clean manner [5][6][7][8] [13,16] including male-specific data [17,18].…”
Section: Cathetersmentioning
confidence: 99%